Informed design decision-making: from digital analysis to urban design. A contemporary approach for the redevelopment of public open spaces - Pezzica, C. (2017)
This paper describes a novel approach to explore public open spaces multidimensional design space and to guide decision-making in the design of highly informed, evidence-based, architectural solutions. It presents an overview of the most relevant design variables and constraints that are useful in planning contemporary and sustainable public open spaces that trace the social and cultural values of local communities. This work aims at providing an holistic guidance for the development of better urban design proposals for the contemporary city environment. More specifically, this work seeks to synchronously characterize urban spaces at a multi-scale and multi-dimensional level, both quantitatively and qualitatively, by collecting contributions from Space Syntax, Public Life Studies, Building Science and Environmental/Comfort Analysis in public open spaces. Many advanced digital tools are used in order to deal with the data and, iteratively, generate and test different design proposals. The proposed methodology is presented through its implementation and testing in the development of a new experimental project for Largo da Graça, a square located in Lisbon historic centre, which is suitable for testing many different design solutions. This experiment generated a digital design workflow with all the steps undertaken to solve the various design problems identified by considering the efficiency targets (centrality, connectivity, enclosure, thermal comfort, security, social equity and interaction). The process comprises a sequence of comparative design tests and records the choices made when dealing with latent information underlying changing conditions in the use of public space and the programmatic malleability of the Portuguese plaza. The adopted design strategy, as well as the examples extracted from the workflow, are used to illustrate the proposed methodology with a hands-on approach. Ultimately, this paper seeks to tight the link between research and sustainable design, adequate for effectively supporting and orientating the planning and design of better public open spaces.